Dispersal of Hoffmannia excelsa (Rubiaceae) by the Toltec fruit-eating bat (Artibeus toltecus) in central Veracruz, México - Colorado-Durán, Wendy Bertha; Espinosa-Francisco, Eduardo Keint; Sierra-Vázquez, Fabiola; Castro-Luna, Alejandro Antonio (Therya Notes, 2022)
In this note we report the fruit consumption and non-endozoochorous seed dispersal of a plant species that had not been mentioned in the diet of bats, and that does not present the typical characteristics of chiropterochory. This event was recorded while conducting night captures with mist nets in fragments of secondary vegetation in the metropolitan area of Xalapa de Enríquez, México. A female specimen of Artibeus toltecus, captured in June 2018 was carrying two fruits of Hoffmannia excelsa (Rubiaceae). Even though H. excelsa is a common shrub in central Veracruz, this is the first known record of dispersal in this species, carried out by bats. The consumption of this fruit, with ornithochorous characteristics, is possibly due to a situation of opportunism in the face of a temporarily abundant resource.